(untitled) (Academia Science Repository, 2023)
In this article, the problem of increasing the competitiveness of construction in the region and the specifics of construction in the conditions of increasing competitiveness, a number of factors of the competitiveness of construction organizations, as well as methods for increasing the competitiveness of construction organizations, as well as suggestions and recommendations for increasing competitiveness in construction are given.